The Social Portrait of the Most Active Communists and Their Supporters in the First Republic of Lithuania - Ėmužis, Marius (Lietuvos istorijos studijos, 2019)
The aim of this article is to provide a social portrait of the most active communists and their supporters who had participated in the illegal underground communist movement during the period of the First Lithuanian Republic (1918–1940). Also, we analyze the question of what socioeconomic conditions led these people to participate in or support the communist underground. The biographies and biographical data of two hundred forty-two individuals (the most active members of the communist party of Lithuania, their supporters, and party leadership from 1926) were researched. The main source for such a study were autobiographies and questionnaires gathered by the former Institute of Party History of Soviet Lithuania. The social portrait was divided by studying the birthplace (city, town, or village), social origins, the situation of the wealth of the family, the education of the person, their marital status, children, occupation, and imprisonment. Many causes (written in autobiographies) of why these individuals joined the communist movement were related to their socialization and social contacts (influence from parents, friends, school, etc.). But it cannot be said that only these causes were relevant. People were also influenced by their social background, education, and the welfare of their families. All these aspects were also interrelated. This problem must be analyzed using a multicausal approach. There was not much quantitative difference between those who were born in the cities or in the villages, but when they began participating in the underground communist movement, their supporters mostly migrated to cities. Most of the analyzed people had come from workers’ families (about 40%) or the peasantry (28%). In total, about 70 percent of them came from quite poor families – 47% of the analyzed individuals described in their autobiographies the poor financial conditions of their upbringing; others also described difficulties, having lost one or both of their parents. However, about 20% wrote that their families lived quite normally, although these individuals still joined the communist movement. This proves that not only the financial situation of families was the deciding factor. The education acquired by these individuals was quite poor, too – about half had only primary education and did go to secondary school but did not finish it. About 13% had finished secondary schools, and only 5% acquired a higher degree diploma. The leadership of the CPL differed, as half of them had finished communist education schools in Moscow before returning to Lithuania. Because of the illegal activities in which they were engaged, many active communists and their supporters did not have families of their own (only 27% were married), and many did not have children (only 15% had a child). Most of the people analyzed were workers; some 9% did not have any long-term occupation, having to hide and move around a lot. About 12% were “professional revolutionaries” engaged in party work and were paid by the party. About 18% were pupils or students (mostly the supporters). Only about 14% worked as teachers, medics, accountants, etc. About half of these people were imprisoned at least once, and about 35% of them were imprisoned longer than 3 months. Party members were imprisoned more often and longer.